The Concept of Sufahā’ in Surah Al-Baqarah Verses 13 and 142: Its Relevance to the Phenomenon of Disinformation in the Digital Era - Selvira Sutra Bella; Komarudin Sassi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the concept of Sufahā’ in Surah Al-Baqarah verses 13 and 142 and its relevance to the phenomenon of disinformation in the digital era. The study employed the tafsir maudhu'i (thematic exegesis) method using theological, epistemological, and contextual approaches within a library research framework. The findings reveal three main points. First, the concept of Sufahā’ refers not only to intellectual ignorance but also to an epistemological crisis characterized by the inability to understand and position truth appropriately. Second, the characteristics of Sufahā’ are reflected in individuals who perceive themselves as unquestionably correct, are reluctant to verify information, and rely on reasoning detached from the guidance of divine revelation. Third, the phenomenon of disinformation in the digital era represents a contemporary manifestation of the characteristics of Sufahā’, as reflected in the dissemination of information without tabayyun (verification). These findings demonstrate that integrating reason and revelation, together with strengthening Qur'anic digital literacy, is highly relevant to fostering critical awareness, moral responsibility, and information verification skills in contemporary digital society.